Evaluation of NH4+ Adsorption Capacity in Water of Coffee Husk-Derived Biochar at Different Pyrolysis Temperatures - Nguyen Van Phuong; Nguyen Khanh Hoang; Le Van Luan; L. V. Tan (International Journal of Agronomy)
Ammonium NH4+ is a pollutant that can be harmful to the water environment. The purpose of this study is to access NH4+ removal capacity from water by coffee husk-derived biochar. The properties of biochar prepared at different temperatures (300, 450, and 600°C) were determined including TOC, and pH, pHpzc, functional groups of H+/OH−, cation-exchange capacity (CEC), and the characteristics of groups of organic matter (FT-IR spectrum) were identified and evaluated. The trend of NH4+ adsorption equilibrium and kinetics of biochar have been studied. The experimental design of adsorption equilibrium was carried out by exposing biochar to a NH4+ solution at different concentrations, ranging from 0 to 50 mg NH4+/L for 12 hours. Kinetic surveys were carried out when biochar was exposed to a solution containing 8.3 mg NH4+/L for a varying length of time. The results showed that Langmuir and Freundlich models and the pseudo-second-order kinetic model are suitable to explain the NH4+ adsorption equilibrium and kinetics on the biochar forms derived from coffee husk. Biochar derived from coffee husk prepared at lower pyrolysis temperature has a higher adsorption capacity. The results suggest that the biochar could be used as an adsorbent ammonium from water.